The Effectiveness of Learning Cycle 7E Model Assisted by Educational Games on Students’ Science Learning Outcomes - Intan Ramadhani Kahar Putri; Achmad Ramadhan; Merry Kristhiani (Equator Science Journal, 2025)
This study aims to investigate the effectiveness of implementing the Learning Cycle 7E model assisted by educational games in improving the learning outcomes of class XI F students at SMA Negeri 2 Palu. The research method applied is Classroom Action Research (CAR), which was conducted in two cycles with a total of 36 student participants. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The material in the first cycle focused on “structure, function, and hormones in the human reproductive system,” while the second cycle discussed “menstruation, fertilization, gestation, and disorders of the human reproductive system.” Data collection was carried out through learning achievement test instruments in the form of pretests and posttests, and the data were analyzed using the percentage of learning mastery. The results revealed that in the first cycle, student mastery increased from 22% (pretest) to 89% (posttest). In the second cycle, the mastery level rose from 17% to 92%. These findings indicate that the implementation of the Learning Cycle 7E model is effective in science learning and has a significant impact on improving student achievement. Overall, it can be categorized as producing a very high level of mastery, proving the potential of integrating the Learning Cycle 7E with educational games in classroom practice.